Effects of health promotion programs on nutritional behavior and hematocrit levels of adolesence pregnant women with anemia in the community - Danpradit, Prapaiwan; Yingpaiboonsuk, Udomporn (Vajira Nursing Journal, 2024)
This research was a quasi-experimental research with two groups pre-test-post-test design. The objectives were to compare nutritional behavior and hematocrit levels after health promotion program between the control and the experiment groups and to compare nutritional behavior and hematocrit levels between pre- and post- health promotion program in the experiment group. The samples included pregnant women under 20 years old who had to attended antenatal care at 16-28 weeks of pregnancy at a public or private hospital, governmental hospitals or private clinics, hematocrit levels below 33% and lived in communities in Nakorn Pathom province. There were 60 samples who were selected by purposive sampling and divided into two groups of 30 samples and assigned to the control and the experiment groups. Research tools were: 1) health promotion program for teenage pregnant women applied from Pender’s conceptual framework and built success experience through video and online media. 2) questionaires of nutritional behavior and hematocrit levels. The samples received health promotion twice at home and twice via telephone or online media. The samples received health promotion twice at home and twice via telephone or online media. The research results showed that, after health promotion program, the experiment group had higher levels of nutritional behavior and hematocrit levels than the control group. In the experiment group, the health behavior and hematocrit levels after health promotion program were higher than health behavior and hematocrit level before the program with statistical significance at 0.01.